The Impact of DJOS Surgery, a High Fat Diet and a Control Diet on the Enzymes of Glucose Metabolism in the Liver and Muscles of Sprague-Dawley Rats - Stygar, Dominika; Andrare, Dorian; Bażanów, Barbara; Chełmecka, Elżbieta; Sawczyn, Tomasz; Skrzep-Poloczek, Bronisława; Olszańska, Ewa; Karcz, Konrad Wojciech; Jochem, Jerzy (Frontiers in Physiology, 2019)
The prevalence of diabetes type 2 (T2DM) is growing exponentially and becoming a global public health problem. The enzymes of glucose metabolism play a role in the pathogenesis of insulin resistance and T2DM. A pathophysiological link between different dietary patterns, obesity, and the enzymes of glucose metabolism can be used as a potential target in therapeutic strategies for the treatment of obesity, and T2DM. The aim of this study was to measure the impact of DJOS surgery and different types of dietary patterns on glycogen synthase kinase 3 α (GSK-3 α), glycogen phosphorylase (PYGM, PYGL), and phosphofructokinase (PFK-1) concentrations in liver and soleus muscle tissues of rats. After 8 weeks on a high-fat diet (HF) or control diet (CD), rats underwent duodenal-jejunal omega switch (DJOS) or SHAM (control) surgery. After surgery, for the next 8 weeks, half of DJOS/SHAM animals were kept on the same diet as before, and half had a changed diet. The concentrations of GSK-3 α, PYGM, PYGL and PFK-1 were measured in the soleus muscles and livers of the Sprague-Dawley rats. The type of diet applied before/after surgery had stronger impact on levels of selected enzymes than DJOS or SHAM surgery. The impact of DJOS surgery was visible for GSK-3α and PYGL concentration in the liver but not in the soleus muscle tissue. The type of surgery had an impact on liver GSK-3α concentration in all studied groups except the CD/CD group, where the impact of diet was stronger. DJOS surgery influenced the level of PYGL in the livers of rats maintained on the CD/CD diet but not from other groups. The dietary patterns applied before and after surgery, had a stronger impact on enzymes’ concentrations than DJOS surgery, and the strong, deleterious effect of an HF diet was observed. A change of the diet per se showed a negative impact on the enzymes’ tissue concentration.